Safety and efficacy of atezolizumab plus bevacizumab in patients with unresectable hepatocellular carcinoma in early clinical practice: A multicenter analysis. Issue 3 (30th November 2021) - Chuma, Makoto; Uojima, Haruki; Hattori, Nobuhiro; Arase, Yoshitaka; Fukushima, Taito; Hirose, Shunji; Kobayashi, Satoshi; Ueno, Makoto; Tezuka, Shun; Iwasaki, Shuichiro; Wada, Naohisa; Kubota, Kousuke; et al.
Abstract: Purpose: To assess the impact of clinical factors on the safety and efficacy of atezolizumab plus bevacizumab (ATZ + BV) treatment in patients with unresectable hepatocellular carcinoma (u‐HCC). Method: Ninety‐four u‐HCC patients who were treated with ATZ + BV at multiple centers were enrolled. We defined Child‐Pugh (CP)‐A patients who received ATZ + BV treatment as a first line therapy as the 'meets the broad sense of the IMbrave150 criteria' group (B‐IMbrave150‐in, n = 46), and patients who received ATZ + BV treatment as a later line therapy or CP‐B patients (regardless of whether ATZ + BV was a first line or later line therapy) as the B‐IMbrave150‐out group ( n = 48). Patients were retrospectively analyzed for adverse events (AEs) and treatment outcomes according to their clinical characteristics, including neutrophil lymphocyte ratio (NLR) at baseline. Results: The overall incidence of AEs was 87.2% (82/94 patients). The frequency of interruption of ATZ + BV treatment due to fatigue was higher in CP‐B than CP‐A patients ( p = 0.030). Objective response (OR) rates of the B‐IMbrave150‐in group (28.3%, 39.1%) were significantly higher than those of the B‐IMbrave150‐out group (8.3%, 18.8%; p = 0.0157, 0.0401) using Response Evaluation Criteria in Solid Tumors (RECIST) and modified RECIST, respectively. In multivariate analysis, NLR (hazard ratio (HR), 4.591; p = 0.0160) and B‐IMbrave150 criteria (HR, 4.108; p = 0.0261) were independent factors associated with the OR of ATZ + BV treatment using RECIST. Conclusion: In real‐world practice, ATZ + BV treatment might offer significant benefits in patients who meet B‐IMbrave150 criteria or have low NLR.